Surface roughness values for resin based materials - Grossman, E. S.; Rosen, M; Cleaton-Jones, P.E; et al (My University, 2004)
INTRODUCTION: Surface roughness of dental restorative materials is most often established with the Ra value obtained using profilometry or by assessing surface topography with the scanning electron microscope (SEM). Both methods should validate each other in confirming surface roughness. AIMS AND OBJECTIVES: The purpose of this study was to compare surface roughness values obtained with a profilometer to the SEM appearance of 6 resin-based restorative materials and assess whether Ra was appropriate as a sole surface roughness measure. Methods Six 5mm diameter specimen discs of Prodigy (Pr); Z100 (Z); Compoglass F (C); Hytac Aplitip (H); Photac-Fil (Pf) and Vitremer (V) were prepared against Mylar strips and stored in distilled water for 14 days. One side of each disc was sequentially polished with Soflex discs to super fine state, the other side remained unpolished. Three surface roughness measurements were made on each surface (n=18) recording Ra, Rv, Rp and Rt values, this data was subjected to a four way ANOVA and Tukey's Studentised Range Test (p=0.05). Two unpolished and two polished discs per material were prepared for SEM, evaluated and visually grouped for surface roughness. RESULTS: Approximate ascending order of roughness was Z, Pr, H, C, V, Pf for Ra, Rv, Rp and Rt and un/polished treatment. Polishing increases surimens into a "bland" (Pr, H, Z, C) and "textured" group (Pf and V). The polished specimens gave four groups: (Pr), (Z and C), (H) and (V and Pf) of increasing surface complexity. Polishing caused surface scratching, removed the matrix, reduced or removed filler particles and exposed voids within the material. CONCLUSIONS: This study emphasises the importance of using more than one technique to assess surface roughness. Rv and Rp values should be utilised to better understand polish induced surface feature changes. Rv maximum is a better measure to identify surface defects which could affect restoration longevity.
KIM
Keywords: Materials Testing; Composite Resins; Resins, Synthetic; Materials Testing